Implementation of Community Satisfaction Index Application to Medan Police Service - Eka Rahayu; Boni Oktaviana Sembiring (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
As a public service provider, the Medan Polrestabes community service unit is faced with many things related to improving the quality of public services through good service performance. To measure the performance of public service units, elements / indicators are needed as a reference to provide an assessment of the performance results of public service units. To determine public satisfaction with services, the government issued several regulations related to the quality of public services, one of which is KEPMENPAN NO.25 / 2004 concerning general guidelines for compiling the community satisfaction index for service units of government agencies, which are general guidelines used as a reference for government agencies. There are 14 indicators related to the performance and services performed by service employees. The purpose of this research is to develop a service quality measurement application that can be accessed directly by the public. With the application of measuring the quality of public services that can be accessed directly by the public, the task of public service providers in evaluating the performance of public service delivery can be carried out easily. Based on the results of the research, the value of the community satisfaction index at the Medan Police Station with 50 respondents as a whole was 3.07572, the IKM value after being converted was 76.893 where the quality of service B and the performance of the service unit were in the good category, meaning that the community was satisfied with the service of the Medan Police.Keyword : Application, Community Satisfaction Index, website